SARS-CoV-2-Specific Adaptive Immunity in COVID-19 Survivors With Asthma - Chen, Li; Yue, Junqing; Zhang, Shengding; Bai, Wenxue; Qin, Lu; Zhang, Cong; Wu, Bihao; Li, Moxuan; Xu, Shuyun; Jiang, Qing; Yang, Lin; Xu, Qingxiu; et al. (Frontiers in Immunology, 2022)
Background: Asthma patients potentially have impaired adaptive immunity to virus infection. The levels of SARS-CoV-2-specific adaptive immunity between COVID-19 survivors with and without asthma are presently unclear. Methods: COVID-19 survivors (patients with asthma n=11, with allergies n=8, and COVID-19 only n=17) and non-COVID-19 individuals (asthmatic patients n=10 and healthy controls n=9) were included. The COVID-19 patients were followed up at about 8 months and 16 months after discharge. The clinical characteristics, lymphocyte subsets, memory T cells, and humoral immunity including SARS-CoV-2 specific antibodies, SARS-CoV-2 pseudotyped virus neutralization assay, and memory B cells were analyzed in these subjects. Results: The strength of virus-specific T cell response in COVID-19 survivors was positively correlated with the percentage of blood eosinophils and Treg cells (r=0.4007, p=0.0188; and r=0.4435, p=0.0086 respectively) at 8-month follow-up. There were no statistical differences in the levels of SARS-CoV-2-specific T cell response between the COVID-19 survivors with, and without, asthma. Compared to those without asthma, the COVID-19 with asthma survivors had higher levels of SARS-CoV-2-specific neutralizing antibodies (NAbs) at the 8-month follow-up (p<0.05). Moreover, the level of NAbs in COVID-19 survivors was positively correlated with the percentage of Treg and cTfh2 cells (r=0.5037, p=0.002; and r=0.4846, p=0.0141), and negatively correlated with the percentage of Th1 and Th17 cells (r=-0.5701, p=0.0003; and r=-0.3656, p=0.0308), the ratio of Th1/Th2, Th17/Treg, and cTfh1/cTfh2 cell (r=-0.5356, r=-0.5947, r=-0.4485; all p<0.05). The decay rate of NAbs in the COVID-19 survivors with asthma was not significantly different from that of those without asthma at 16-month follow-up. Conclusion: The level of SARS-CoV-2-specific NAbs in COVID-19 survivors with asthma was higher than that of those without asthma at 8-month follow-up. The SARS-CoV-2-specific T cell immunity was associated with blood eosinophils and Treg percentages. The SARS-CoV-2-specific humoral immunity was closely associated with cTfh2/cTfh1 imbalance and Treg/Th17 ratio. According to the findings, asthmatic patients in COVID-19 convalescent period may benefit from an enhanced specific humoral immunity, which associates with skewed Th2/Th1 and Treg/Th17 immune.